2020
DOI: 10.1103/physreve.101.023313
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a hydrogen atom in a laser field using the time-dependent variational principle

Abstract: The time-dependent variational principle is used to optimize the linear and nonlinear parameters of Gaussian basis functions to solve the time-dependent Schrödinger equation in 1 and 3 dimensions for a one-body soft Coulomb potential in a laser field. The accuracy is tested comparing the solution to finite difference grid calculations using several examples. The approach is not limited to one particle systems and the example presented for two electrons demonstrates the potential to tackle larger systems using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Rowan et al showed that only their counterparts with time-dependent parameters are able to reasonably describe the wavefunction propagation in laser fields. 134 Recently, Coccia and co-workers have decided to revisit and extend the work of Kaufmann et al with the primary goal of constructing basis sets for an accurate description of atomic and molecular HHG spectra. 131,[135][136][137][138][139] They combined the K functions with augmented Dunning basis sets 140 containing a very large number of diffuse functions.…”
Section: Introductionmentioning
confidence: 99%
“…Rowan et al showed that only their counterparts with time-dependent parameters are able to reasonably describe the wavefunction propagation in laser fields. 134 Recently, Coccia and co-workers have decided to revisit and extend the work of Kaufmann et al with the primary goal of constructing basis sets for an accurate description of atomic and molecular HHG spectra. 131,[135][136][137][138][139] They combined the K functions with augmented Dunning basis sets 140 containing a very large number of diffuse functions.…”
Section: Introductionmentioning
confidence: 99%
“…Now, gaussians are very flexible, which means that there may be several distinct LCGs that approximate the same wavefunction to a very high accuracy, i.e., the nonlinear parameters are almost redundant. This leads to the system of ODEs being very stiff, and time-propagation with the Dirac-Frenkel variational principle is therefore very challenging for the LCG ansatz [4].…”
Section: The Methods Of Vertical Linesmentioning
confidence: 99%
“…Perhaps ironically, the flexibility of the LCG wavefunctions make them very hard to propagate using the standard Dirac-Frenkel variational principle [2], leading to ill-conditioned variational equations [3,4]. The propagation scheme described in this Letter is based on the method of vertical lines, or Rothe's method [5,6].…”
Section: Introductionmentioning
confidence: 99%